PENGEMBANGAN BUKU SUPLEMEN KIMIA BAHAN ALAM PADA MATERI SKRINING FITOKIMIA TANAMAN GENUS PREMNA PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS MUHAMMADIYAH PONTIANAK - saidah jambak; dini hadiarti; raudhatul fadhillah (Universitas Muhammadiyah Pontianak, 2019)
By far, learning sources and materials used by the lecturers in Chemistry of Natural Materials class haven’t met the students’ needs, as teachers only used power point, text books, and scientific articles during the teaching-learning process. Therefore, it is important to develop the complete learning materials, such as supplementary books. This study focused on the validity of supplementary book for Chemistry of Natural Sciences Class of Phytochemical Screening of Gemnus Premna in terms of materials (content), media, and small group try out. Using Research and Development (R&D) Model of Dick & Carey, as well as the references from Pambudiono (2016) and Puspitasari (2016), this study implemented a number of steps. They were identifying the learning purposes, conducting the learning analysis, analyzing the students and the context, formulating the specific learning purposes, developing the assessment instrument, developing the learning strategies, developing and selecting the learning materials, designing and developing the formative evaluation, and revising the product. As many as 15 students of Chemistry Education participated as the samples. The data collection techniques were direct communication (interview), observation, and post test questions.The study revealed the material or the content of the supplementary book was valid by 98,6%. It was measured by the content validity, the presentation, and the language use. Similarly, based on the results of media expert, the supplementary book was also valid by 70,62%, measured by the book cover, book design, rules of writing, and feasibility of presentation. Last but not least, the results of the small group try out showed the book was valid by 84,18%, in terms of attractiveness, comprehensibility, and level of difficulty